Exploring the Role of Religiosity in Moderating Employee Commitments in Islamic Banking (Study at Sharia Banks in East Java, Indonesia) - R Iqbal Robbie; Khusnul Rofida Novianti (TSAQAFAH, 2020)
AbstractIslamic banking has increased rapidly in Indonesia for the last ‎few decades. As a country with Moslem domination religion, ‎religiosity is considered as one of the essential determinants ‎for Moslem consumers to using Islamic/sharia banking ‎products. The primary purpose of this paper is to analyze and test ‎the influence of organizational culture, especially the ethical ‎values dominated by the influence of Javanese and Madura ‎culture on employee organizational commitment and ‎performance, and to examine how the influence of religiosity as ‎a moderating variable on the relationship between commitment ‎organizational and employees of performance. Data were obtained from 109 employees working in the sharia banking (both state-owned and private sharia bank) located in Jember, East Java. Data were collected through a questionnaire carried out from August to September 2019 and analyzed using PLS software. The findings indicate the ethical value ‎of the company does not have a significant influence on ‎organizational commitment, and the variable of religiosity turns ‎out to play a significant role in increasing the interaction ‎between organizational commitment to employee performance. ‎This paper contributes to show the importance of religiosity ‎aspects that needs to be maintained to ensure increased ‎employee performance.‎Keywords: Religiosity, Ethical Values, Organizational Commitment, Performance. AbstrakPerkembangan perbankan syariah mengalami peningkatan yang sangat pesat dalam beberapa dekade terakhir. Sebagai negara dengan dominasi agama Islam, faktor religiusitas menjadi pertimbangan penting bagi konsumen Muslim dalam menggunakan produk perbankan syariah. Artikel ini bertujuan menganalisis dan menguji pengaruh budaya organisasi khususnya nilai etis yang didominasi dari pengaruh budaya Jawa dan Madura terhadap komitmen organisasi dan kinerja karyawan serta menguji pengaruh religiusitas dalam memoderasi pengaruh antara komitmen organisasi dan kinerja karyawan. Data diperoleh dari 109 karyawan yang bekerja di sektor perbankan syariah (baik bank syariah milik BUMN maupun bank syariah swasta) yang berada di Kabupaten Jember, Jawa Timur. Data dikumpulkan melalui kuesioner yang dilaksanakan sejak Agustus hingga bulan September 2019 dan dianalisis menggunakan software PLS. Hasil dari penelitian ini menunjukkan bahwa nilai etis perusahaan tidak memiliki pengaruh signifikan terhadap komitmen organisasi dan religiusitas memiliki peran penting dalam meningkatkan interaksi antara komitmen organisasi dan kinerja karyawan. Artikel ini berkontribusi dalam menunjukkan pentingnya aspek religiusitas yang perlu dikelola dalam memastikan peningkatan kinerja karyawan.Kata Kunci: Religiusitas, Nilai Etis, Komitmen Organisasi, Kinerja.